Atomic-scale simulation of structure and mechanical properties of Cu1−xAgx|Ni multilayer systems. (15th May 2018) - Gola, Adrien; Gumbsch, Peter; Pastewka, Lars
Abstract: We use a combination of atom-swap Monte-Carlo (MC) and molecular dynamics (MD) to study the structure and mechanical properties of C u 1 − x Ag x | Ni multilayers with 6 nm layer width for which the Ag-content is used to tune the lattice misfit. We find that the multilayers form a semi-coherent interface with a network of partial dislocations arranged in a regular triangular pattern. A combination of MC and MD was used to equilibrate C u 1 − x Ag x | Ni with x = 0%, 5% and 10%. Ag does not enter the Ni-layer but segregates and precipitates from the Cu layers. We find alloying of Cu and Ni at 600 K. All these findings are in good agreement with the experimental binary phase diagrams of the Cu-Ag, Ag-Ni and Cu-Ni systems. The resulting multilayer structures were then sheared parallel and perpendicular to the normal of the bilayer interface. Initial sliding takes place at the Cu|Ni interface within the misfit dislocation network, followed by emission of partial dislocations into the Cu layer. Flow stress increases with increasing Ag content. Additional calculations of biaxial tension that suppress sliding at the heterointerface show a similar trend. Strengthening can be attributed to Ag precipitates pinning the Cu|Ni heterointerface and to the formation of sessile stacking-fault tetrahedra from the misfit dislocation network whose density increases with the concentration of Ag in the Cu layer. Graphical abstract: Image 1